Opioid Prescriptions at Hospital Discharge Are Associated With More Postdischarge Healthcare Utilization. Issue 3 (5th February 2019) - Liberman, Justin S.; Samuels, Lauren R.; Goggins, Kathryn; Kripalani, Sunil; Roumie, Christianne L.; ,
Abstract : Background: Many patients use opioids for nonmalignant pain, and opioid use in the general population has been associated with poor long‐term outcomes. The use of high‐risk medications, including opioid analgesics, may increase the risk of unplanned healthcare utilization. Methods and Results: We performed a nested evaluation in the VICS (Vanderbilt Inpatient Cohort Study) (N=3000) on patients with an admitting diagnosis of acute coronary syndrome and/or acute decompensated heart failure. Patient enrollment occurred from October 2011 until December 2015 and involved a single investigational site, Vanderbilt University Medical Center (Nashville, TN). Of the 2495 eligible patients, 501 (20%) were discharged with an opioid prescription and were predominantly white and men, with a median age of 59 (interquartile range, 53–67) years. Our primary outcome was unplanned healthcare utilization, which included emergency department presentation or readmission. Secondary outcomes included mortality and a composite of planned utilization behaviors: cardiac rehabilitation and provider follow‐up within 30 days. Cox proportional hazards models did not show a statistically significant association with increased unplanned utilization (adjusted hazard ratio, 1.06; 95% CI, 0.87–1.28) or mortality (adjusted hazard ratio, 1.08; 95% CI, 0.84–1.39), compared with those without opioids at discharge. Patients discharged with opioids were less likely to complete planned healthcare utilization (adjusted odds ratio, 0.69; 95% CI, 0.52–0.91). Conclusions: There are decreased odds of planned healthcare utilization among patients with acute coronary syndrome and acute decompensated heart failure discharged with opioid medication. It is imperative to understand how opioid use can affect a patient's relationship with the healthcare system.